Contribution à l’étude des caractères climatiques et bioclimatiques dans la région de Mostaganem. - MORTET, Fethi Abdallah; MAMAR, Fatima (My University, 2021)
Climate is an essential parameter in biological and ecological studies. to the explanation of the functioning of ecosystems. Our study aims to describe the climatic and bioclimatic parameters of the Mostaganem region. We noted three climatic parameters : temperature, rainfall, and humidity rate and over a period of 31 years (1989-2020). Our results indicate that 2006 is the hottest year. Climate analysis shows that the Mostaganem region has not experienced a change in the temporal variation of the parameters studied. Despite its position near a hydrological dam (Oued Chlef) is positioned in a semi-arid climatic stage.
Keywords: Mostaganem, climat, température, pluviométrie, Humidité